anonymous
  • anonymous
problem # 10. g(x)=log(x+5) when g(x)=5 help please
Mathematics
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

amistre64
  • amistre64
g(x) = log(x+5) g(x) = 5 ; therefore 5 = log(x+5)
cwrw238
  • cwrw238
oopps!!
cwrw238
  • cwrw238
amis is right

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

amistre64
  • amistre64
now if log means base 10 10^5 = x+5 10^5 - 5 = x
anonymous
  • anonymous
so the answer would be x=99995. thx!
anonymous
  • anonymous
for the same problem but g(x-3) so i started by (x-3)=log (x+5)?? is that correct how iam doing it? the professor has two answers g(x+3)=log(x+2)i dont know how he got it.
amistre64
  • amistre64
g(x+3) is different in that it defines "x" to be a certain .... value? x = "x+3" sooo g(x+3) = log((x+3)+5) g(x+3) = log(x+8)
amistre64
  • amistre64
it helps if I read it right to begin with
amistre64
  • amistre64
g(x-3) is the same concept tho g(x-3) = log((x-3)+5) g(x-3) = log(x-3+5) g(x-3) = log(x+2)
amistre64
  • amistre64
in the first bit of your post; it says g(x) = yadayada in the second bit it says x = yadayada such that: g(x) = log(x+5) g(x-3) = log((x-3)+5)
anonymous
  • anonymous
so what are you doing is g(x-3)=log (x+5).(x-3) is that what it is? iam a little confused, sorry.

Looking for something else?

Not the answer you are looking for? Search for more explanations.